1981
DOI: 10.1111/j.1365-2672.1981.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Enumeration of Listeria monocytogenes from Sewage, Sewage Sludge and River Water

Abstract: Listeria monocytogenes in sewage, sewage sludge and river water was isolated by enrichment at 4°C with subculture and enrichment in thiocyanate, naladixic acid broth and plating on to Tryptose Agar. The results indicated that L. monocytogenes is present in sewage and sewage sludge in considerable numbers and that this organism survives longer than Salmonella spp. on land sprayed with sewage sludge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
136
1
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(149 citation statements)
references
References 13 publications
10
136
1
2
Order By: Relevance
“…We found Listeria species present in water samples less often than in some of the above studies [11,13], but at about the same rate as others [12,15]. Whilst we examined only 100 ml volumes, studies that have quantitated the presence of Listeria spp.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…We found Listeria species present in water samples less often than in some of the above studies [11,13], but at about the same rate as others [12,15]. Whilst we examined only 100 ml volumes, studies that have quantitated the presence of Listeria spp.…”
Section: Resultssupporting
confidence: 63%
“…Whilst we examined only 100 ml volumes, studies that have quantitated the presence of Listeria spp. in water found counts sufficiently high to be detected by this lower volume [11,16]. The most probable explanation for the lower isolation rate in this study was that the waters examined tended to be relatively free from faecal contamination and did not receive sewage effluents.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Based on our results, we suggested that the bulk storage tank on farm A was a very important source of secondary contamination of raw milk with L. monocytogenes beside the previously recognized sources such as the environment [6,22,23], feed [6,18], cattle feces [13] and wild life [1,6,9]. It is not possible to eliminate L. monocytogenes in the cattle intestines or from the environment.…”
mentioning
confidence: 99%
“…Previous studies have confirmed the presence of L. monocytogenes in water of rivers and lakes (Dijkstra, 1982;Watkins & Sleath, 1981), and additional information confirmed that growth initiation is dependent of inoculum size (Genigeorgis & Riemann, 1979). We investigated the ability of growth of L. monocytogenes in a water system, using a small initial numbers of organisms, to support our major study with defensins in the same system.…”
Section: Introductionmentioning
confidence: 75%